Pengaruh Gaya Kepemimpinan Transformasional dan Kerja Sama Tim terhadap Kinerja Pegawai pada Kantor Badan Penanggulangan Bencana Daerah (BPBD) Kabupaten Sikka - Lusia Emiliana Lawi; Imanuel Wellem; Maria Modesta Missi Mone (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to: (1) describe employee performance, transformational leadership style, and team collaboration: (2) analyze the influance of transformational leadership style and team collaboration on employee performance both partially and simultaneously. The population of this study comprised 35 employees from the Regional Disaster Management Agency (BPBD) Office of Sikka Regency. Due to the limited population, acensus or saturated sampling method was employed. Data were collected through questionnaires and analyzed using descriptive and inferential statistical methods, specifically multiple linear regression. Hypothesis testing was conducted using F-test and t-test. Descriptive analysis results indicate that the employee performance variable was categorized as good, the transformational leadership style variable as good, and the team collaboration variable as good. The statistical test results show that partially, the transformational leadership style variable had a positive and significant influance on employee performance. Additionally, the team collaboration variable had a positive and significant influence on employee performance. The F-test results indicate that simultaneously, both transformational leadership style and team collaboration variables significantly influence empployee performance. The determination analysis results indicate that both independent variables in this study explain 37,60% of the variability in the fluctuation of employee performance at the Regional Disaster Management Agency (BPBD) Office of Sikka Regency.